Production and Characterization of Activated Carbon from Waste Eggshell - Adam Iqmal Razman Shah; Lochena Devi Santharan; Muhammad Nazmi Alif Mohd Najib; Nilavarasi Muniswaran; Abu Bakar, Norhaliza (Multidisciplinary Applied Research and Innovation, 2024)
The utilization of waste materials for the synthesis of value-added products has gained considerable attention due to its economic and environmental benefits. In this study, an investigation into the production and characterization of activated carbon derived from waste eggshells is presented. The abundance of eggshell waste from various sources provides a promising opportunity for sustainable waste management and resource utilization. The production process involves a two-step approach: calcination of eggshells to obtain calcium oxide (CaO), followed by chemical activation using a potassium hydroxide (KOH) activation agent. The effects of activation temperature i.e. 500°C, 650°C and 800°C were systematically studied to optimize the porous structure and adsorption properties of the activated carbon. The resulting activated carbon was characterized using a range of techniques including scanning electron microscopy (SEM) and Fourier-transform infrared spectroscopy (FTIR). The porous structure of the activated carbon exhibited a high surface area and well-developed porosity, making it suitable for various applications including adsorption, water treatment, and gas separation. The results demonstrated the potential of waste eggshell-derived activated carbon as an efficient adsorbent for dye removal, attributing its adsorption capability to the presence of surface functional groups and the porous structure. The activated carbon produced with temperature 650°C is the most ideal activated carbon compared to other activated carbon produced with different temperature.